Training locomotor function: From a perspective of the underlying neural mechanisms - Ogawa, T.; Kanosue, K. (Sports Performance, 2015)
In a variety of sports activities and in our daily lives, we utilize locomotory movements such as walking and running. It is well understood that maintaining and improving their function can be of major significance in the acquisition of a better sports performances and a more fulfilling life. To facilitate appropriate changes in performance, it is essential to know the basic mechanisms underlying them. In the case of the basic locomotory movements, their neuronal control mechanisms are predominantly automatic and quite different from those that underlie voluntarily-induced movements. A number of studies in the last several decades have described the characteristic features and responsible mechanisms in both animals and humans. On the basis of the knowledge obtained in these studies, this chapter will review the recently acquired knowledge to elucidate the neural mechanisms underlying execution of locomotion movements and provide information for construction of possible intervention for improvement in their performance.